Midterm results of endovascular aortic repair in patients with hostile neck - Kaptanıderya Tayfur (Turkish Journal of Vascular Surgery, 2020)
Objectives: This study aims to investigate the feasibility of endovascular aortic aneurysm repair (EVAR) in patients with a hostile aortic neck anatomy. Patients and methods: Between July 2010 and September 2019, a total of 54 patients (18 males, 36 females; mean age 77.0±6.2 years; range 63 to 89 years) with a hostile neck anatomy (proximal aortic neck angulation >60°; proximal aortic diameter >28 mm; proximal aortic length [Turk J Vasc Surg 2020; 29(1.000): 43-9]